# When x=7, 5-3(x-1)= ?

### 7 Answers | Add Yours

To evaluate the expression, plug-in the value of x.

`5-3(x-1)`

`=5-3(7-1)`

From here, follow the order of operations which is PEMDAS, So,simplify the expression insides the parenthesis.

`=5-3(6)`

Then, multiply.

`=5-18`

And subtract.

`=-13`

**Hence, when `x=7` , `5-(x-1)=-13` .**

`5-3(x-1)=5-3x+3=5+3-3x=8-3x`

`8-3x=8-3*7=8-21=-13`

When x=7, => -13

5-3(x-1)=? x=7

5-3(7-1)

5-3(6)

5-18

-13

When x=7, 5-3(x-1)= ?

so substitute 7 in the place of x

5-3(7-1) follow pemdas and simplify

5-3(6) subtract 1 from 7

5-18 multiply 3*6

-13 subtract 18 from 5

If x = 7 then 5 - 3 ( x - 1 )=

First plug in 7

By plugging in 7, your equation should look like

**5 - 3 ( 7 - 1 ) **Now subtract 7 and 1

By subtracting, your equation should look like

**5 - 3 ( 6 ) **Now distribute the 3

By distributing, your equation should look like

**5 - 18 **Lastly just subtract 5 with 18

By subtracting you should get

**= -13 **which is your answer

Plug it in

x=7, 5-3(x-1)= ?

5-3(7-1)=5-3(6)

By the Order of Operations

5-18=

**-13**

x=7, 5-3(x-1)=

5-3(7-1)

5-3(6)

5-18=-13

**-13**